THE LINGUACULTURAL REPRESENTATION OF THE CONCEPT EDUCATION-UPBRINGING IN THE PROSE OF ABDULLA QODIRIY TA'LIM-TARBIYA KONSEPTINING ABDULLA QODIRIY NASRIDA LINGUAMADANIY NAMOYISHI - Soatov Ibrohimbek Alisherovich (Western European Studies, 2024)
This study explores the linguacultural representation of the concept of education-upbringing (ta'lim-tarbiya) in the prose of Abdulla Qodiriy, a seminal figure in Uzbek literature. Using a qualitative content analysis approach, the research examines key linguistic patterns, cultural themes, and cognitive frameworks in Qodiriy’s works, particularly focusing on “O‘tkan Kunlar” and other notable texts. The findings highlight how Abdulla Qodiriy employs symbolic and metaphorical language to convey traditional values, societal expectations, and moral principles, deeply rooted in Uzbek cultural and historical contexts. Cognitive analysis reveals conceptual metaphors, such as "growth as enlightenment," that underpin the depiction of education-upbringing as a cornerstone of individual and social development. This study contributes to linguacultural and literary studies by demonstrating how Qodiriy’s prose not only reflects but also reinforces cultural norms and schemas related to education-upbringing. The implications extend to understanding the role of literature in preserving and promoting cultural identity. Future research could expand this analysis to include comparative studies with other Uzbek authors or cross-cultural perspectives.
Keywords: education-upbringing; ta'lim-tarbiya; Abdulla Qodiriy